Producing framework tree species for restoring forest ecosystems in Northern Thailand - Elliott S. (2014)
Since 1994, the Forest Restoration Research Unit of Chiang Mai University's Biology Department (FORRU-CMU) has been developing methods to restore forest ecosystems to deforested sites within protected areas, for biodiversity conservation and environmental protection in northern Thailand. With support from WWF Greater Mekong Thailand Country Programme and corporate sponsor King Power Duty Free, the unit is working with Hmong hill tribe villagers from Baan Mae Sa Mai, in Doi Suthep-Pui National Park, to expand a demonstration site for the 'framework species method' of forest restoration. The technique entails planting 20 to 30 indigenous forest tree species, capable of rapidly shading out weeds and attracting seed-dispersing animals from nearby forest remnants. This results in rapid increase in tree species richness, progressing towards the species composition of the original forest, as well as overall biodiversity recovery. FORRU-CMU operates a research tree nursery, where innovative tree propagation techniques are developed, and a community-based nursery and education centre, where the practicability of those techniques is tested by local villagers. The nurseries and the demonstration field trials have become a popular training facility where visiting foresters and conservationists, both from Thailand and neighbouring countries, can learn effective forest restoration methods. FORRU-CMU provides a model for formulating a strategy to apply the framework species method to restore larger degraded sites within Thailand's protected areas system. © Steve Harrison, John Herbohn 2008.